Industrial production of microbial protein products. (June 2022) - Banks, Mason; Johnson, Rob; Giver, Lori; Bryant, Geoff; Guo, Miao
Graphical abstract: Highlights: Bioprocess design of microbial protein technologies and optimisation spaces. Industrial landscape including key players and market trends. Case study focused on gas fermentation to illustrate challenges in optimisation and scale-up of novel processes. Process integration and intensification as a means of improving sustainability and economics of microbial protein production. Abstract : Microbial proteins provide a sustainable and nutritious alternative to traditional animal and plant-based proteins. Various strains have been demonstrated to generate biomass from a wide variety of substrates, from organic waste (e.g. banana peel) to gases (e.g. methane). Industrial production of microbial protein has proven difficult from both design (e.g. production rate) and regulatory (e.g. allergenicity of product) perspectives for both feed and food-grade products. Through use of low-cost microfluidics devices, early bioprocess design can be intensified, achieving high strain screening throughput with low titres. Integration of industrial waste streams (e.g. flue-gases, lignocellulosic residues) can reduce cost and carbon footprint of feedstock, while bespoke reactor design (e.g. Quorn's airlift U-loop fermenter) can remediate issues of low mass-transfer and product quality.